2011
DOI: 10.1007/s00167-011-1696-5
|View full text |Cite
|
Sign up to set email alerts
|

How much of the PCL is really preserved during the tibial cut?

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
55
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 16 publications
1
55
0
Order By: Relevance
“…Several studies have drawn attention to how much of the PCL is actually preserved in a CR TKA, with several of them showing that most of the PCL insertion may be disrupted during the tibial cut, calling into question how much of the PCL is actually preserved. 24,[30][31][32][33][34] Liabaud et al used magnetic resonance imaging (MRI) to show that the majority (79.8%) of patients had more than 50% of the PCL destabilized following a standard transverse tibial cut. 30 Shannon et al also using MRI demonstrated that up to one-third of patients had complete removal of the PCL insertion.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have drawn attention to how much of the PCL is actually preserved in a CR TKA, with several of them showing that most of the PCL insertion may be disrupted during the tibial cut, calling into question how much of the PCL is actually preserved. 24,[30][31][32][33][34] Liabaud et al used magnetic resonance imaging (MRI) to show that the majority (79.8%) of patients had more than 50% of the PCL destabilized following a standard transverse tibial cut. 30 Shannon et al also using MRI demonstrated that up to one-third of patients had complete removal of the PCL insertion.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the sMCL may be a more important restraint than the PCL at low flexion angles in CR‐TKA, and thus why the knees in this study did not meet the hypothesis stated, which was based on studies with native, non‐injured PCL knees . A study showing that between 45% and 69% of the tibial PCL attachments were found to have been resected during standard CR‐TKA tibial cuts, which may reduce the amount of load that the PCL can carry and therefore its usefulness in a clinical setting, although in this study there was no visible damage to the PCL. It is clear however that if the PCL is completely ruptured there would be instability in posterior drawer especially at higher flexion angles, and a posterior–stabilized (PS) TKA with a post‐cam mechanism would be needed to restore stability.…”
Section: Discussionmentioning
confidence: 72%
“…Several methods have been described to balance the ligaments and releasing the PCL completely may result worse outcomes [18,19,20,21]. Some studies have drawn attention that most PCL insertions may be destroyed during tibia cutting, and which raises questions about how much PCL actually saves in a CR TKA [18,[22][23][24][25][26]. Eric Kim et al [10] studied the incidence and risk factors of PCL avulsion during CR TKA, they found the incidence is 1.7% and female gender was the only risk factor.…”
Section: Discussionmentioning
confidence: 99%